Foreword - Sarmento, Elsa de Morais (Journal of Economic Development, Environment and People, 2013)
The entry into a non-expansionary phase of the economic cycle, caused by the financial and economic crisis raised serious budgetary constraints to most countries since 2009, and reopened a debate that reconsiders the institutions and rules governing the functioning of markets. However, even in times of crisis, it is fundamental not to neglect the growth potential of policies that promote green and sustainable development, especially when the global landscape is being reconfigured by new technological paradigms, a new set of players and a high degree of uncertainty...